2020
DOI: 10.1177/1559827620916699
|View full text |Cite
|
Sign up to set email alerts
|

The First, Comprehensive, Open-Source Culinary Medicine Curriculum for Health Professional Training Programs: A Global Reach

Abstract: Providing a strong foundation in culinary medicine (CM)—including what constitutes a healthy diet and how to find, obtain, and prepare healthy and delicious food—is a cornerstone of educating health professionals to support patients in achieving better health outcomes. The Culinary Medicine Curriculum (CMC), published in collaboration with the American College of Lifestyle Medicine, is the first, comprehensive, open-source guide created to support the implementation of CM at health professional training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Reasons for excluding articles reviewed as full-text included wrong study design ( n = 13) [ 4 , 12 – 23 ], wrong population ( n = 5) [ 24 28 ], a failure to report any outcome measures ( n = 3) [ 9 , 29 , 30 ], wrong intervention ( n = 3) [ 26 , 31 , 32 ], and five studies were found to be duplicates of an included paper or had used the same data ( n = 5) [ 33 37 ]. Amongst the 24 included studies, there were six qualitative studies [ 38 43 ], four cross-sectional studies [ 34 , 44 46 ]; seven case studies [ 47 – 53 ], and seven mixed-methods study [ 35 , 54 – 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for excluding articles reviewed as full-text included wrong study design ( n = 13) [ 4 , 12 – 23 ], wrong population ( n = 5) [ 24 28 ], a failure to report any outcome measures ( n = 3) [ 9 , 29 , 30 ], wrong intervention ( n = 3) [ 26 , 31 , 32 ], and five studies were found to be duplicates of an included paper or had used the same data ( n = 5) [ 33 37 ]. Amongst the 24 included studies, there were six qualitative studies [ 38 43 ], four cross-sectional studies [ 34 , 44 46 ]; seven case studies [ 47 – 53 ], and seven mixed-methods study [ 35 , 54 – 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent scoping review by Asher et al, 2021 explored literature that provides culinary and nutrition training to and by health, education, and culinary professionals. This study demonstrated that the feasibility and outcomes of culinary medicine programs warrant further investigation as there is still insufficient evidence of the impact these programs on practitioners to promote health behaviour changes in patients [ 4 ] and the viability of culinary medicine [ 9 ]. This scoping review aims to synthesise the existing literature on culinary medicine offered to medical students within their four years of medical school education.…”
Section: Introductionmentioning
confidence: 99%
“…Reading, online videos, and lectures enabled students to learn some of the science behind culinary medicine. Students were assigned to read the Introduction to the Culinary Medicine Curriculum, 14 and five chapters from Beth Frates’ “Lifestyle Medicine Handbook” (viz, Understanding Lifestyle Medicine, Empowering People to Change, Collaborating, Motivating, Goal Setting and Tracking, and The Nutrition-Health Connection). 17 Experts from within and outside KSOM presented one-hour lectures with discussions.…”
Section: Methodsmentioning
confidence: 99%
“…The foundation of the program was the 9 culinary medicine sessions in the CMC 14 (see Table 2). These comprehensive sessions provide detailed information on preparing for and conducting each session.…”
Section: Culinary Skillsmentioning
confidence: 99%
See 1 more Smart Citation